PEMADANAN NIK – NPWP DAN PELAPORAN SPT TAHUNAN ORANG PRIBADI OLEH RELAWAN PAJAK - Fathin Amirah; Iman Supriadi (PUTRA JAWA PUBLISHER, 2023)
This research investigates the Tax Volunteer program, a collaborative effort between the East Java Regional Tax Office I and local universities like STIE Mahardhika Surabaya. The program's primary goal is to assist taxpayers with their Annual Income Tax Return (SPT Tahunan) submissions while also educating them about transitioning from the National Identification Number (NIK) to the Tax Identification Number (NPWP). Employing a multifaceted methodology encompassing surveys, interviews, and document analysis, this study offers a comprehensive assessment of the program's effectiveness. The findings reveal a substantial increase in taxpayer awareness regarding the NIK to NPWP transition, a consequence of the dedicated efforts of tax volunteers. Furthermore, the research posits that this heightened awareness has the potential to expedite the creation of a Single Identification Number (SIN), which could simplify and streamline tax-related administrative processes. This study underscores the pivotal role played by collaborative partnerships between tax authorities and educational institutions in enhancing tax compliance and administration. These collaborative endeavors are not only crucial for taxpayer education but also carry significant implications for the future evolution of tax policies and improvements in service delivery. By strengthening these partnerships, society stands to benefit from more efficient and accessible tax procedures.